Developing Photonovella Adventure Media to Improve Primary Students' Storytelling of Place Where I Live Theme (Journal of Primary Education, 2018)
The study aims to determine the characteristics and effectiveness of photonovella adventure media development for improving the storytelling skills with the place where I live as the theme in high-class students at elementary school. This study used a qualitative approach in the form of data development needs and quantitative in the form of test scores referring to the rubric of the assessment of storytelling skills. Trials were conducted twice, i.e. limited trials and implementation tests. The implementation test was conducted in grade 4 at three elementary schools. The result of this research is characteristic of development of photonovella adventure media has 3 principles based on aspect of development requirement, that is usage effect principle, content of story photonovella, media of story telling. The improvement of storytelling skills can be determined using normalized gain. The result of N-gain calculation showed that the value of g = 0.704, it means that there is a significant increase. The result shows tvalue is 16.616 and ttable is 1.67 which means that the media of photonovella adventure can be applied effectively. The conclusion is the media of photonovella adventure has 3 characteristic principles, and it is also effective for the improvement of storytelling skills.